(untitled) (ItalianoLinguadue, 2016)
Nel Vocabolario milanese italiano è presente non solo un ricchissimo vocabolario bilingue della cucina ma una vera e propria enciclopedia alimentare (prodotti, ingredienti, mestieri, piatti): un cantiere aperto e di enorme importanza per la storia della nostra cultura linguistica e gastronomica, sia prima dell’Unità sia dopo l’Unità d’Italia. Dining with Cherubini. A work in progress The Vocabolario milanese italiano not only features a very rich range of terms regarding cooking but it is also a veritable encyclopedia of food (products, ingredients, professions, dishes): a work in progress of huge importance for the history of our culture, language and cuisine, both before and after the unification of Italy.